Perencanaan Perbaikan Kualitas Layanan Jasa Wisata Menggunakan Pendekatan Integrasi Servqual dan Quality Function Deployment - Ahmad Mubin (Department Industrial Engineering, University of Muhammadiyah Malang, 2008)
Competition of tourism business in Malang makes the recreational park management to improve their innovations. Innovation intended to how the management can increase the quality of service which is able to give significant advantages and differs from the others recreational park. Sengkaling Recreational Park is one of tourist destination in Malang which is quite a lot visited by tourists. But since the exist of another competitor the Jatim Park, causes the decreased of the number of visitors of the Sengkaling Recreational Park. Therefore research was needed to be done to know what kind of service attributes wanted by tourists and how is the difference condition between perceptions and tourist expectations to quality of service given. A planning method which applicable to translate the customer needs become the action plan form for company is QFD. This step can be use to evaluate and plan the improvement of service quality. To sharpen the identification of service quality attributes that need to be applied therefore QFD approach is integrated with Servqual approach. At the Servqual approach found nine service attributes which have negative gap (difference) between perceptions and tourist expectations, that is security and safety guarantee of the play arena, the complete of the play arena, availability of toilet, hygiene and less time to pass on the toilet, comfortable route tourism object, supporting facilities for health and safety, environmental safety of tourism object, availability of dangerous area guide, and hygiene environment of tourism area. To plan the improvement of service quality, through QFD approach from result of analysis HOQ is got from priority consumer desire based on percentage rating of Normalized Raw Weight which is the complete of plays arena (15.09%), comfortable route of tourism object (13.10%), security and safety guarantee of plays arena (12.45%) and availability of the toilet (11.73%). While technical response which given high priority to be repaired and improved to fulfill satisfaction of Sengkaling Recreational Park visitors that is elegibility test of plays arena equipments and supporting facilities in routine (97.323), renovation of toilet building (96.513), addition of toilet in strategic locations (93.697), installation of commemoration fringes or sign in all area of the tourism object (70.033), location of officer cleaning service effectively (66.227) and addition of arena facility plays at (57.982).